Imitation Model of Development of Communication and Information Services for The Population of The Region - Nosirov Bakhtiyor Nusratovich (Genius Journals, 2022)
The article discusses the areas of services, econometric models for the development of communication and information services to the population, in particular, the model of imitation, and makes suggestions and recommendations based on the results obtained
Keywords: Service sector; econometric modeling; imitation model; communication and information services